Spectroscopic Characterization and Theoretical Treatment of Tetradentate Macrocyclic Ligand and Its Transition Metal Complexes - H. Sh. Al-Obaidi, Omar (Asian Journal of Chemistry, 2012)
Manganese(II), cobalt(II), nickel(II) and copper(II) complexes were synthesized with a novel tetradentate ligand viz. 2,9-dithioxo-1,3,8,10-tetraazacyclotetradecane-4,7,11,14-tetraone (L). All the complexes were characterized by analytical and spectral methods such as FT-IR, electronic spectral studies, magnetic susceptibility measurements, atomic absorption, molar conductivity measurements, molar ratio studies and melting points. The molar conductance measurements of the complexes in DMSO correspond to be non-electrolytic nature for all prepared complexes. On the basis of FT-IR and electronic spectral studies all complexes display an octahedral geometry around the metal center, whereas tetragonal for Cu(II) complexes in (1:1) ( L:M). A theoretical treatment of the formation of complexes in the gas phase was studied, this was done using the HYPERCHEM-6 program for the molecular mechanics and semi-empirical calculations. The free ligand and its complexes have been tested for their antibacterial activities against two type of human pathogenic bacteria: (Staphylococcus aureus), (Escherichia coli). The first are Gram positive while the second are Gram negative (by using agar well diffusion method). Finally, it was found that compounds show different activity of inhibition on growth of the bacteria.